RNA N6-methyladenosine methylation in influenza A virus infection - Liu, Xueer; Chen, Weiqiang; Li, Kangsheng; Sheng, Jiangtao (Frontiers in Microbiology, 2024)
Influenza A virus (IAV) is a negative-sense single-stranded RNA virus that causes acute lung injury and acute respiratory distress syndrome, posing a serious threat to both animal and human health. N6-methyladenosine (m6A), a prevalent and abundant post-transcriptional methylation of RNA in eukaryotes, plays a crucial regulatory role in IAV infection by altering viral RNA and cellular transcripts to affect viral infection and the host immune response. This review focuses on the molecular mechanisms underlying m6A modification and its regulatory function in the context of IAV infection and the host immune response. This will provide a better understanding of virus‒host interactions and offer insights into potential anti-IAV strategies.